Determinasi Teknologi terhadap Media Televisi Net. dan TVRI Lampung - Sinaga, Hendriko Daulat; Rahayu, Vera Shovi (Jurnal Mahardika Adiwidia, 2023)
Technological determination has an impact on social media activities, one of the social media affected by the impact of technological determination is television media NET. and TVRI Lampung. To complete the New Media and Journalism Lecture assignments at Sahid University Jakarta lectures, this research will reveal the problems faced by NET. TV and TVRI Lampung in facing technological determination, namely; 1) Does Net. TV and TVRI Lampung tend to lead to the integration of the YouTube medium or the use of other media. 2) How to maintain the value of the news they present still needed? To answer these questions, research on the impact of technological determination on the Net. TV and TVRI Lampung were conducted by the researcher. The method used in this research uses descriptive qualitative analysis, which is a study method used to reveal facts, circumstances, phenomena, variables, and conditions that occur when the research runs and displays information as it is. Qualitative descriptive research through literature studies and interviews that have been conducted by other researchers is expected to be able to reveal the influence of technological determinations on NET. TV and TVRI Lampung.